Legal Framework for Financial Achieving Efficiency in Government Spending During Economic Crises : A Legal Study on Rationalizing Expenditures and Ensuring Financial Sustainability (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Objectives. This study aims to analyze public spending governance and ensure financial sustainability by reviewing the legal framework regulating public expenditures and the role of oversight bodies in achieving financial compliance. Materials and Methods. The study employed a literature review method by examining relevant legal documents, public policies, and reports from oversight institutions. A descriptive analysis was conducted to evaluate the impact of economic crises on public spending policies and expenditure rationalization strategies. Results. The findings indicate that implementing financial governance principles, including transparency, accountability, and efficiency, plays a crucial role in achieving financial balance and economic sustainability. Long-term financial planning and the development of flexible policies effectively reduce deficits and promote economic growth. Conclusions. The study recommends strengthening financial legislation, empowering oversight bodies, and adopting innovative and sustainable financial strategies to ensure efficient public spending and optimal utilization of financial resources.